2017
DOI: 10.4049/jimmunol.1602087
|View full text |Cite
|
Sign up to set email alerts
|

IL-24 Promotes Pseudomonas aeruginosa Keratitis in C57BL/6 Mouse Corneas

Abstract: The aim of this study was to elucidate the expression and functions of interleukin (IL)-24 in C57BL/6 mouse corneas in response to Pseudomonas aeruginosa (PA) infection. Among IL-20R cytokines, only IL-24 was induced at both mRNA and protein levels by infection at early time points. The upregulation of IL-24 was dampened by flagellin pretreatment, which protects the corneas from microbial infection. Time course studies revealed bimodal early and later peaks of IL-24 expression, a pattern shared with SOCS3 but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 58 publications
2
10
0
Order By: Relevance
“…Using antibody neutralization, we showed that downregulating TSLP-TSLPR signaling significantly augmented corneal opacification, clinical scores, bacterial burden, PMN infiltration, and the expression of IL-1β at 3 dpi. The bacterial plate counts for the controls of P. aeruginosa toxic strain at 3 dpi are within the ranges reported in the literature 31 , 32 as well as our previous studies, 18 , 26 even though the number of bacteria used to inoculate the mouse corneas were 100-fold less than that used by others. 21 , 31 The differences in the detected bacterial burden between the control and TSLPR-neutralized corneas at 3 dpi (∼10 fold with P = 0.0198) is comparable to our previous study of the corneas treated with recombinant IL-24.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Using antibody neutralization, we showed that downregulating TSLP-TSLPR signaling significantly augmented corneal opacification, clinical scores, bacterial burden, PMN infiltration, and the expression of IL-1β at 3 dpi. The bacterial plate counts for the controls of P. aeruginosa toxic strain at 3 dpi are within the ranges reported in the literature 31 , 32 as well as our previous studies, 18 , 26 even though the number of bacteria used to inoculate the mouse corneas were 100-fold less than that used by others. 21 , 31 The differences in the detected bacterial burden between the control and TSLPR-neutralized corneas at 3 dpi (∼10 fold with P = 0.0198) is comparable to our previous study of the corneas treated with recombinant IL-24.…”
Section: Discussionsupporting
confidence: 87%
“…At 3 dpi, heavy opacity covered the entire cornea with corneal ulceration, melting ring, and neovascularization (reddish color), pathologies usually seen in the control corneas at day 5. 18 , 26 The clinical scores revealed significantly higher disease severity in the TSLPR neutralizing antibody-treated group than that observed in the IgG injected control group (6.2 vs. 11.6 at 3 dpi; Fig. 4 A).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Many organisms, including P. aeruginosa , are able to undergo mutation to acquire resistance to antimicrobial peptides, which would enhance their ability to persistently infect epithelial surfaces. An important site of P. aeruginosa infection is the eye, where these organisms are an important cause of keratitis [34, 35]. A major therapeutic strategy against these biofilm infections is the development of optimized antimicrobial peptides delivered topically [36].…”
Section: P Aeruginosa Resistance To Antimicrobial Peptidesmentioning
confidence: 99%
“…Unlike IL-20, IL-24 may suppress mucosal inflammation by inducing suppressor of cytokine signaling (SOCS) 3 expression in HT-29 colonic epithelial cells and membrane-bound mucin (MUC)-1, −3, and −4 in human colonic subepithelial myofibroblasts obtained from patients with IBD [44]. IL-24 also exacerbates Pseudomonas aeruginosa infection in mouse corneas by promoting SOCS3 expression, which leads to the suppression of anti-bacterial molecules expression, including S100A8/A9 and IL-1β [48]. …”
Section: Immunobiology Of the Il-20r Cytokinesmentioning
confidence: 99%